Abdominal cocoon (Pulse, 2014)
Background The abdominal cocoon syndrome was first described as a rare condition where part of or the whole small bowel is encased within a fibrous membrane. Idiopathic sclerosing encapsulating peritonitis (or abdominal cocoon) is a rare cause of small bowel obstruction, especially in adult population. Diagnosis is usually incidental at laparotomy. But preoperative diagnosis can be made. Case presentation This report is of a 27-year-old Bangladeshi male who presented with increasing abdominal pain and features of subacute intestinal obstruction. He had a history appendicectomy 2 months back through grid iron incision in a peripheral hospital. Pre-operative work-up did not reveal a sac like structure encasing small intestinal loops. At computed tomography of the abdomen and pelvis, a huge cystic structure was seen encasing loops of small bowel. At laparotomy, a fibrous capsule was revealed, in which small bowel loops were encased, with the presence of interloop adhesions. A diagnosis of primary abdominal cocoon was established and extensive adhesiolysis was performed. The patient had an uneventful recovery and follow-up. No evidence of Kochs noted in the abdomen or on histopathology of tissue sent for examination. Conclusion Abdominal cocoon is a rare cause of small bowel obstruction, but should be suspected especially in cases with attacks of non strangulating obstruction in the same individual. A high index of clinical suspicion may be generated by the recurrent character of small bowel obstruction. Clinicians must rigorously pursue a preoperative diagnosis. The overall prognosis is satisfactory. DOI: http://dx.doi.org/10.3329/pulse.v5i2.20269 Pulse Vol.5 July 2011 p.61-64